Literasi Keuangan untuk Menumbuhkan Kecerdasan Finansial Mahasiswa - Kurnianti, Destria; Khairunnisa, Hera; Handarini, Dwi; Marsofiyati; Anwar, Choirul; Dianta, Karuniana; Yusuf, Muhammad; Mundhiharno; Yaacob, Mohd Hasimi; Malzara, Vidia Ratu Balqis; Sari, Rini Nurmala; Haneul; Safitri, Gita (Bahasa Indonesia, 2024)
This community service is aimed to teach students about the important role of financial literacy in shaping students' understanding of personal financial aspects. The participants of this activity is students of the Faculty of Economics, Universitas Negeri Jakarta. To teach financial literacy to students, the research team invited a lecturer speaker and a speaker from Finansialku as a digital financial application to give knowledge about about financial planning, investment, and debt management. The outcome of this event is the findings that provide insight into the effectiveness of financial literacy training and its potential impact on students' financial lives. Abstrak Pengabdian masyarakat ini bertujuan untuk mengajarkan kepada mahasiswa tentang peran penting literasi keuangan dalam membentuk pemahaman mahasiswa terhadap aspek keuangan pribadi. Peserta kegiatan ini adalah mahasiswa Fakultas Ekonomi Universitas Negeri Jakarta. Untuk mengajarkan literasi keuangan kepada mahasiswa, tim peneliti mengundang pembicara dosen dan pembicara dari Finansialku sebagai aplikasi keuangan digital untuk memberikan pengetahuan mengenai perencanaan keuangan, investasi, dan pengelolaan utang. Hasil dari kegiatan ini adalah temuan yang memberikan wawasan tentang efektivitas pelatihan literasi keuangan dan potensi dampaknya terhadap kehidupan keuangan mahasiswa.